Responsible Consumption Behavior, Crucial Goals for Sustainable Development: A Systematic Review and Future Research Prospects - Gunawan, Arie Indra; Gaffar, Vanessa; Bansah, Pearl Fafa; Monoarfa, Hilda (Jurnal Internasional Penelitian Bisnis Terapan, 2024)
Responsible consumption has been recognized as one of the efforts to achieve the SDGs, but it still requires much refinement, and at the moment, there is little time left until 2030 to achieve the SDGs. The academic literature is carried out through the PRISMA method, analyzing the study descriptively and thematically, and performing analysis synthesis to report the study results. The findings of this study are that the concept of responsible consumer behavior in a sustainable context has evolved in a more specific direction, no longer being a general statement of direct support for the SDGs. However, its implementation focuses on consumers' consumption consciousness to make their choices wiser, influenced by various internal and external factors. Based on the study we have drawn up a framework for developing research topics on sustainable behavior so that further research can quickly implement research themes across various industrial sectors and from multiple perspectives.